Analyzing Sembalun Village's Potential as an Agrotourism Attraction - Muhammad Adi Junaidi; Fitri Amir, Ahmad; Rochmi, Evilia; Amrullah, Amrullah; Solihin, Riadatus; Walid Sugandi, Yogi Birrul (JMET: Journal of Management Entrepreneurship and Tourism, 2024)
Sembalun Village boasts abundant natural resources, yet only Mount Rinjani has been fully developed to its maximum potential. Therefore, it is crucial to explore and analyze the various potentials that Sembalun Village possesses for agrotourism development. This study aims to identify these potentials and their implications for the community in developing agrotourism attractions. The research employs a qualitative descriptive approach to provide an in-depth overview of the conditions and potential for agrotourism development in Sembalun Village. Data collection was conducted through three primary techniques: participatory observation, in-depth interviews, and documentation. The results indicate that Mount Rinjani and its surroundings have significant potential for integrated tourism development. The hills around Sembalun Village offer spectacular views that attract photography enthusiasts. Developing photography spots with supporting facilities can enhance the tourist experience. Additionally, the fields and plantations offer refreshing natural tourism experiences. The development of integrated tourism packages with agrotourism can provide a richer experience for tourists and economic benefits for the local community.